Social processes as the missing link: cross-sectionally testing a conceptual model on social mediators of early psychopathological development - Achterhof, Robin; Kirtley, Olivia J.; Lafit, Ginette; Hiekkaranta, Anu P.; Hagemann, Noëmi; Hermans, Karlijn S. F. M.; Lecei, Aleksandra; Boets, Bart; Henquet, Cécile; Schneider, Maude; Sips, Rob; Vaessen, Thomas; et al. (Psychological medicine, 2024)
BackgroundResearch suggests that most mental health conditions have their onset in the critically social period of adolescence. Yet, we lack understanding of the potential social processes underlying early psychopathological development. We propose a conceptual model where daily-life social interactions and social skills form an intermediate link between known risk and protective factors (adverse childhood experiences, bullying, social support, maladaptive parenting) and psychopathology in adolescents - that is explored using cross-sectional data.MethodsN = 1913 Flemish adolescent participants (Mean age = 13.8; 63% girls) were assessed as part of the SIGMA study, a large-scale, accelerated longitudinal study of adolescent mental health and development. Self-report questionnaires (on risk/protective factors, social skills, and psychopathology) were completed during class time; daily-life social interactions were measured during a subsequent six-day experience-sampling period.ResultsRegistered uncorrected multilevel linear regression results revealed significant associations between all risk/protective factors and psychopathology, between all risk/protective factors and social processes, and between all social processes and psychopathology. Social processes (social skills, quantity/quality of daily social interactions) were uniquely predicted by each risk/protective factor and were uniquely associated with both general and specific types of psychopathology. For older participants, some relationships between social processes and psychopathology were stronger.ConclusionsUnique associations between risk/protective factors and psychopathology signify the distinct relevance of these factors for youth mental health, whereas the broad associations with social processes support these processes as broad correlates. Results align with the idea of a social pathway toward early psychopathology, although follow-up longitudinal research is required to verify any mediation effect.
Gesehen am 14.04.2025